Indikator kesejahteraan perancangan bandar Islam - Lagiman, Norizam (2015)
An ideal city and urban wellbeing should be based on an appropriate framework for planning of an urban society. Previous studies on urban planning were based on indicators obtained from the perspective of western countries. The indicators used are based on physical, economy and social dimensions. Presently, no study has been done onindicators of urban wellbeing from an Islamic perspective. The objective ofthe study was to develop a set of indicators from an Islamic perspective suitable for measuring the level of wellbeing of an urban area. Initially, a preliminary set of indicators based on the study of al-Quran, al-Sunna, review of literature and views from Islamic scholars was developed. A total of 109 respondents among Muslim scholars participated in evaluating the indicators in the first Delphi survey and in the second Delphi survey only 70 respondents returned the questionnaires. Data were analysed using Statistical Package for Social Science (SPSS) version 18.0. The T-test was used to test the hypothesis on whether there were differences of view on the indicators among scholars at a significant level of p<0.05. Analysis of the results from the Delphi study endorsed 96 indicators without any significant conflicting views among the Islamic scholars who had participated in the study. The set of indicators was validated through its application in Muar and Batu Pahat towns in Johor,using data collected from a surveyof 600 respondents living in the towns and secondary information. After going through the validation process, 7 indicators were dropped from the list due to problems with data availability and appropriateness of the indicators in the context of local situation and practices. This study produced 89 indicators for an urban wellbeing based on Islamic principles and these indicators encompass physical, economy, social (western perspective), with the addition of theology, moral and institutional dimensions. The study also calculated the urban wellbeing of Muar to be higher than Batu Pahat. As a conclusion, this study recommends ways to improve the urban wellbeing for both towns based on Islamic principles indicators and highlights the future role of Islamic religious institutions.